Aktivitas Kegiatan SD Muhammadiyah 019 Bangkinang Kota Melalui Program PLP oleh Mahasiswa Universitas Muhammadiyah Riau - Dego Akbar Raimando; Perawati Perawati (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2025)
Students gain practical experience in the world of education through the Introduction to School Field Programme and gain a better understanding of the school environment. This service activity combines lecture theory with real educational practice. The methods used by students include observation, participation in teaching and learning activities, discussions with teachers and students, and documentation. The results of this service show that students have a better understanding of learning methods, classroom management, and problems faced by teachers in elementary schools. In addition, schools also benefit from the assistance provided by students in the learning process. SD Muhammadiyah 019 Bangkinang Kota is the place for this PLP activity. The principal is Mr Musta'in, S.Pd, located at Jalan Muhammadiyah Bangkinang District, Kampar Regency, Riau 28463. The implementation of PLP began on 13 January 2025 and ended on 23 February 2025.